Approaches for Learning Collective Nouns Proficiency: A Case of a South African Primary School - Nephawe, Farisani Thomas (Institut Agama Islam Negeri Palopo, 2025)
Proficiency in the use of collective nouns is indispensable in English because it enhances effective communication. However, using collective nouns appropriately poses challenges to many. The present study investigated approaches for learning collective noun proficiency at a South African primary school. A quantitative research method was espoused as it establishes cause-and-effect relationships and determines a large population’s opinions. Data was collected using a questionnaire because it gathers information from large data sets within a short period. A probability sampling technique was employed to randomly select twenty-five Grade 7 English First Additional Language learners because it gives every learner an equal chance of participation in the study. A Statistical Package for Social Sciences Version 28 was employed to enhance power analysis procedures that create a graphical representation of results. Preliminary investigation indicated that the participants were incompetent in understanding the use of collective nouns. Nonetheless, after using the memory and Scavenger hunt game approaches, learners performed outstandingly. The current study has significant implications for future collective noun proficiency for both learners and teachers. Future researchers can conduct further research on approaches for enhancing collective noun usage. The paper endorses the frequent use of the identified approaches to enhance English proficiency.